Factors associated with developing symptomatic HIV-associated sensory neuropathy - Wadley, Antonia Louise (My University, 2014)
HIV-associated sensory neuropathy (HIV-SN) is one of the most common neurological problems of HIV. It is frequently painful and reduces quality of life. HIV-SN can be caused both by HIV itself and by exposure to neurotoxic antiretrovirals such as stavudine. The South African Department of Health now recommends use of tenofovir in place of stavudine as first line treatment. However many people remain on stavudine and or live with the side effects. Stavudine is still prescribed in many other resource-poor countries. This thesis presents the first systematic study of clinical and genetic risk factors for the development of symptomatic HIV-SN in Black Southern Africans. I recruited 404 Black HIV-positive Africans from the Virology Clinic of the Charlotte Maxeke Academic Hospital, Johannesburg and assessed HIV-SN using the AIDS Clinical Trials Group (ACTG) Brief Peripheral Neuropathy Screen. HIV-SN was defined as present if the patient had both symptoms and signs of peripheral neuropathy. If present, the distribution and intensity of symptoms were recorded. Of those exposed to stavudine, 57% (226/395) had HIV-SN. Pain was the most common symptom and was experienced by 74% (172/226). Of these, 76% (128/172) reported their pain as moderate to severe. As in previous studies, increasing age and height were independently associated with risk of HIV-SN. However nadir and current CD4 T-cell counts and sex were not associated with SN. Patients donated blood for DNA extraction and single nucleotide polymorphisms (SNPs) were selected from the literature and genotyped using Illumina Golden GateTM technology. 342 individuals were assessed for genetic associations with HIV-SN and a subset of 159 positive for HIV-SN were assessed for associations with painful HIV-SN. I completed four genetic analyses: SNPs and haplotypes from TNF and adjacent genes from the major histocompatability complex on chromosome six were assessed for association with HIV-SN. I found no association with TNF-1031, even though this had associated with risk of HIV-SN in Caucasian, Chinese and Malay cohorts. Novel associations were identified between HIV-SN protection and 5 other SNPs (BAT1 rs3130059, rs2523504; ATP6V1G2 rs2071594; NFKBIL1 rs2071592, rs2071591). Associations were also found with haplotypes: FV15-23 weakly associated with risk and FV30-31 associated with protection against HIV-SN in this cohort. Analysis of 8 SNPs not previously assessed produced two novel associations with LTA SNPs (rs1041981, rs909253), where the minor alleles conferred protection against HIV-SN. Analysis of linkage disequilibrium (LD) suggests that there is linkage disequilibrium within the TNF block, that it differs between ethnicities and that TNF-1031 is unlikely to be a causative SNP for risk of HIV-SN. SNPs from other cytokines and chemokines implicated in the pathogenesis of HIVSN and the associated pain were assessed in Chapter 5. The major allele of the antiinflammatory gene IL4 (rs2243250) associated with risk of HIV-SN. This allele has been associated with higher CD4 T-cell counts, so I have proposed a role for high IL- 4 in early stage HIV-SN. A 3-SNP haplotype of IL10 associated with protection against HIV-SN whilst another IL10 haplotype showed a trend for risk of painful HIVSN. These data and the involvement of TNF haplotype (Chapter 4) suggest an inflammatory etiology for HIV-SN. Polymorphisms of UCP2 (rs659366) and UCP3 (rs1800849) have previously associated with risk of diabetic neuropathy. These SNPs encode uncoupling proteins 2 and 3 which regulate reactive oxygen species and may affect development of neuropathy via the effects of oxidative stress and mitochondrial dysfunction. Alleles of these SNPs did not associate with HIV-SN in this cohort. Patterns of linkage disequilibrium may differ between the two ethnicities or UCP2 and UCP3 may associate with a mechanism particular to diabetic neuropathy. I also assessed a ‘pain protective haplotype’ and SNPs of GCH1 which have been associated with decreased pain intensity in radicular pain following lumbar discectomy. Associations of the 3-SNP ‘pain protective’ haplotype (rs10483639*C, rs3783641*A and rs8007267*T) and a 6-SNP haplotype containing this motif with protection against pain were significant but dependent on age, sex and CD4 T-cell count. Association of another 3-SNP haplotype (rs10483639*G, rs3783641*T and rs8007267*C) with increased risk of pain in HIV-SN was also not independent of age, sex and CD4 T-cell count. The weaker associations here compared to Caucasian cohorts may be a result of differing LD between ethnicities or demonstrate different pain mechanisms between HIV-SN and radicular pain following lumbar discectomy. My results highlight the prevalence of HIV-SN and frequency of pain in this Southern African cohort. The genetic studies identify a likely inflammatory component and identify genes worthy of further investigation both in HIV-SN and the associated pain.
Keywords: Sense Organs; HIV-1